Preservice Teacher Perceptions of School Field Introduction Program for Achieving Sustainability in Education: A Survey at Universitas Ahmad Dahlan - Fitria Ningsih; Panji Hidayat; Ega Asnatasia Maharani; Satrianawati Satrianawati (Journal of Education for Sustainable Development Studies, 2024)
School field introduction program is intended to solidify academic and educational field competencies through various activities in schools. The aim of this research is to analyze the various responses of students in the Elementary School Teacher Education Study Program at Universitas Ahmad Dahlan towards the School Field Introduction Program (PLP) II, and to identify internal and external factors that can act as supports or obstacles for students in the implementation of the PLP II program in partner schools or laboratory schools for achieving sustainability in education. This research is quantitative with a descriptive approach and utilizes a survey method. The population of this research includes active odd-semester students in the Elementary School Teacher Education Study Program at Universitas Ahmad Dahlan, class of 2016, totaling 324 students. The sample size was determined using the Slovin formula with a 5% margin of error, resulting in a sample size of 179 student respondents. Data collection was conducted online using a questionnaire. The collected data was analyzed descriptively and presented in percentages using SPSS. The results of this study show that the responses of students in the Elementary School Teacher Education Study Program at Universitas Ahmad Dahlan towards the PLP II program are categorized as very high, with a percentage of 42.5%. The research findings on internal and external factors are also categorized as very high, with percentages of 58.9% and 62.0%, respectively, indicating that internal and external factors can serve as support for the PLP II program. Thus, this research can serve as a benchmark for the success of students in implementing the PLP II program for achieving sustainability in education.